Saxagliptin improves glycaemic control and C‐peptide secretion in latent autoimmune diabetes in adults (LADA). Issue 3 (28th October 2015) - Buzzetti, R.; Pozzilli, P.; Frederich, R.; Iqbal, N.; Hirshberg, B.
Abstract: Background: To assess the efficacy and tolerability of saxagliptin and C‐peptide secretion in patients with diagnosed type 2 diabetes classified as glutamic acid decarboxylase antibody (GADA)‐positive or GADA‐negative. Methods: Post hoc analysis of data pooled from five randomized, placebo‐controlled, 24‐week phase 3 studies ( n = 2709) was conducted. We evaluated mean change from baseline at week 24 in HbA1c, fasting plasma glucose, postprandial plasma glucose, fasting and postprandial C‐peptide, and HOMA2‐%β and the proportion of patients achieving HbA1c < 7% (53 mmol/mol) at week 24. Results: Saxagliptin produced greater adjusted mean reductions from baseline in HbA1c versus placebo for GADA‐negative [difference vs placebo (95% CI), −0.62% (−0.71% to −0.54%); −6.8 mmol/mol (−7.8, −5.9)] and GADA‐positive patients [−0.64% (−1.01% to −0.27%); −7.0 mmol/mol (−11.0, −3.0)]. Consistently, saxagliptin produced a greater reduction from baseline in fasting plasma glucose and postprandial plasma glucose versus placebo in GADA‐positive versus GADA‐negative patients, and more patients achieved HbA1c < 7% (53 mmol/mol) with saxagliptin versus placebo in both GADA‐negative and GADA‐positive patients. Saxagliptin increased β‐cell function as assessed by HOMA2‐%β and postprandial C‐peptide area under the curve from baseline in patients in both GADA‐positive and GADA‐negative patients. Adverse events and hypoglycaemic events were similar across treatment groups and GADA categories. Conclusion: Saxagliptin was effective in lowering blood glucose levels and generally well tolerated in GADA‐positive patients. Interestingly, saxagliptin appears to improve β‐cell function in these patients, although a longer treatment duration may be needed to confirm this finding. Copyright © 2015 John Wiley & Sons, Ltd.